2022
DOI: 10.7554/elife.79898
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of Hsp27 and phosphorylated Tau mitigates abnormal Tau aggregation-induced pathology

Abstract: Amyloid aggregation of phosphorylated Tau (pTau) into neurofibrillary tangles is closely associated with Alzheimer’s disease (AD). Several molecular chaperones have been reported to bind Tau and impede its pathological aggregation. Recent findings of elevated levels of Hsp27 in the brains of patients with AD suggested its important role in pTau pathology. However, the molecular mechanism of Hsp27 in pTau aggregation remains poorly understood. Here, we show that Hsp27 partially co-localizes with pTau tangles in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Molecular chaperone is an important element in controlling the protein quality ( Hartl et al, 2011 ). Several proteins have been reported to, respectively, bind and exert chaperone functions in the aggregation of α-synuclein, tau, TDP-43 and FUS amyloids ( Burmann et al, 2020 ; Li et al, 2022 ; Lu et al, 2022 ; Zhang et al, 2022 ). For example, Hsp27 is reported to effectively reduce the aggregation of tau in vitro ( Baughman et al, 2018 ), and rescue tau pathology in transgenic drosophila and mouse models ( Abisambra et al, 2010 ; Zhang et al, 2022 ).…”
Section: Perspective Mechanisms Underlying Co-pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular chaperone is an important element in controlling the protein quality ( Hartl et al, 2011 ). Several proteins have been reported to, respectively, bind and exert chaperone functions in the aggregation of α-synuclein, tau, TDP-43 and FUS amyloids ( Burmann et al, 2020 ; Li et al, 2022 ; Lu et al, 2022 ; Zhang et al, 2022 ). For example, Hsp27 is reported to effectively reduce the aggregation of tau in vitro ( Baughman et al, 2018 ), and rescue tau pathology in transgenic drosophila and mouse models ( Abisambra et al, 2010 ; Zhang et al, 2022 ).…”
Section: Perspective Mechanisms Underlying Co-pathologiesmentioning
confidence: 99%
“…Several proteins have been reported to, respectively, bind and exert chaperone functions in the aggregation of α-synuclein, tau, TDP-43 and FUS amyloids ( Burmann et al, 2020 ; Li et al, 2022 ; Lu et al, 2022 ; Zhang et al, 2022 ). For example, Hsp27 is reported to effectively reduce the aggregation of tau in vitro ( Baughman et al, 2018 ), and rescue tau pathology in transgenic drosophila and mouse models ( Abisambra et al, 2010 ; Zhang et al, 2022 ). It is possible that those molecular chaperones could bind and stabilize different proteins, but the chaperon functions are variable to different proteins, leading to the co-pathogenesis.…”
Section: Perspective Mechanisms Underlying Co-pathologiesmentioning
confidence: 99%
“… 10 Tau phosphorylation at Ser262 and Ser356 was previously shown to promote phosphorylation at other Alzheimer’s disease-associated phospho-epitopes such as AT100 (phosphorylation at Thr212 and Ser214) and AT8 (phosphorylation at Ser202 and Thr205). 11 Tau phosphorylation at Ser262 and Ser356 affects its interactions with chaperone complexes and degradation, 12 , 13 intracellular distribution, 14 and liquid–liquid phase separation. 15 Substitution of these sites by non-phosphorylatable alanines dramatically reduces tau toxicity in Drosophila models, 11 , 16 , 17 suggesting that phosphorylation at these sites is critical for tau toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that NMDA receptor activity‐dependent dynamic microtubule invasion into the spine can promote spine enlargement and induce a long‐lasting enhancement of synaptic transmission (Hoogenraad & Akhmanova, 2010; Hu et al, 2008; Jaworski et al, 2009), which contributes to the pathogenesis of neuropathic pain (Ji et al, 2003; Kuner, 2010; Wilson et al, 2005). Because of their high expression levels in the brain (Drewes et al, 1997), MARK1 and MARK2 were widely studied for their roles in dendrite and spine morphogenesis, and they were found to contribute to the plasticity of microtubules needed for normal functionality of neuronal dendrites and spine phenotypes (Biernat et al, 2002; Wu et al, 2012; Zhang et al, 2022). In addition, MARK2 knockout mice show decreased learning and memory ability and other phenotypes (Segu et al, 2008), and MARK1 is overexpressed in certain brain regions of autistic patients (Maussion et al, 2008).…”
Section: Introductionmentioning
confidence: 99%